2014
DOI: 10.1111/resp.12415
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD8 T‐cell granzyme B in COPD is suppressed by treatment with low‐dose azithromycin

Abstract: We provide further evidence for the application of low-dose azithromycin as an attractive adjunct treatment option for controlling epithelial cell apoptosis, abnormal airway repair and chronic inflammation in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that the increase of CD8+ T cells is a negative factor for COPD patients, and even in some studies, it has been suggested that the application of small dose of azithromycin can reduce the number of CD8+ T cells in the alveolar lavage fluid of COPD patients, reduce the level of granulosin B released by CD8+ T cells in the peripheral blood, and improve the cellular immunity of COPD patients [ 30 ]. In this study, CD8+ T level was upregulated after autoimmune cell therapy, which has not been seen in other previous studies on the treatment of COPD, and the literature on autoimmune cell therapy of COPD is limited, so the reasons for the increase of CD8+ T level and the advantages and advantages of the increase of CD8+ T level on COPD still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the increase of CD8+ T cells is a negative factor for COPD patients, and even in some studies, it has been suggested that the application of small dose of azithromycin can reduce the number of CD8+ T cells in the alveolar lavage fluid of COPD patients, reduce the level of granulosin B released by CD8+ T cells in the peripheral blood, and improve the cellular immunity of COPD patients [ 30 ]. In this study, CD8+ T level was upregulated after autoimmune cell therapy, which has not been seen in other previous studies on the treatment of COPD, and the literature on autoimmune cell therapy of COPD is limited, so the reasons for the increase of CD8+ T level and the advantages and advantages of the increase of CD8+ T level on COPD still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The granzyme B pathway is a major mediator of cytotoxic T cell induced apoptosis and DNA fragmentation in target cells including airway epithelial cells. A 12 week study by Hodge and colleagues found that low‐dose azithromycin can reduce production of the cytotoxic mediator granzyme B by CD8 + T cells from both airway and intra‐epithelial compartments. This suggested that low‐dose azithromycin may be an adjunct treatment option for controlling epithelial cell apoptosis, abnormal airway repair and chronic inflammation in COPD, although the possible development of microbial resistance and long term benefit needs to be addressed in larger studies.…”
Section: Copdmentioning
confidence: 99%
“…Treatment with erythromycin has been found to decrease neutrophil and lymphocyte counts, lower levels of IL-8 and TNF-α in the BALF, and downregulate keratinocyte-derived chemokine and TNF-α transcription in CS-exposed mice 21,26. Emerging evidence shows that macrolides could play an immunomodulatory role in addition to the known antibiotic role, including the regulation of innate and adaptive immune cells 40,41. We previously showed that erythromycin modulated inflammatory immune cells in the airway and restored the decrease of Treg through immunomodulation in rats exposed to cigarette smoke 26.…”
Section: Discussionmentioning
confidence: 99%